Basic Profile of Child Marriage in Uganda - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of child marriage are high in Uganda. The share of women ages 18-22 who married as children is 36.5 percent, but it has declined over time. The share of girls marrying very early, before the age of 15, has also declined. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. This brief has provided a basic profile of child marriage in Uganda. Measures of child marriage are high. The share of women ages 18-22 who married as children is 36.5 percent, but it has declined substantially over time. The share of girls marrying very early, before the age of 15, has also declined. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects. This brief has provided a basic profile of child marriage in Uganda. Measures of child marriage are high. The share of women ages 18-22 who married as children is 36.5 percent, but it has declined substantially over time. The share of girls marrying very early, before the age of 15, has also declined. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.